User Management for Cloud Computing–Based Computer Laboratory Utilization at SMK Muhammadiyah 2 Palembang - ALBIRR DO KOETY; IRWANSYAH (Jurnal Jaringan Komputer dan Keamanan, 2024)
User management is a systematic process that regulates how users perform tasks within an information system. This process includes the creation of user profiles, the assignment of user roles, the determination of access rights, and the control of user activities. Cloud computing, as a technology that utilizes internet-based servers for data storage and processing, has become increasingly important in supporting data accuracy, speed, and efficiency in various organizational environments. However, many educational institutions still lack an optimal understanding and implementation of this technology. This study aims to design and implement a cloud computing–based user management system for the computer laboratory at SMK Muhammadiyah 2 Palembang. The proposed system utilizes private cloud storage through OwnCloud running on the Linux Ubuntu operating system. The implementation is intended to address issues related to data security, misuse of laboratory facilities, and data loss caused by shared storage media. The results demonstrate that the implemented cloud-based user management system enhances data security through authentication mechanisms, improves the efficiency of data management, and reduces operational costs related to software and hardware maintenance.